Stan i znaczenie harmonizacji rachunkowości sektora publicznego w Unii Europejskiej - Bednarek, Piotr (State and Importance of Harmonization of Public Sector Accounting at the European Union, 2007)
The New Public Management (NPM) is a cluster of techniques that guides the public sector towards modernization and innovation. Accountancy is one of the matters being reformed. In the recent years, local governments have initiated, with different intensities, important changes in their accounting systems. Nevertheless, these changes have had different effects in each country and this affects comparability. Harmonization tries to allow comparison by eliminating differences. In this paper, firstly, the author analyzes the degree of harmony between the annual account of European Union local governments, on the basis of research results available in the literature. Secondly, the author identifies the importance of harmonization process of public sector accounting for European Union countries.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 19-28